Analysis of the Quality of Public Services on Imported Consigned Goods for Use in Realizing Excellent Service at KPPBC Type C Intermediate Customs Post Office Pasar Baru in 2018 - Eko Tjahjono; Pebriana Arimbhi (Yayasan Ilomata, 2022)
Public services are seen as evidence of a direct relationship between the government and the community in providing the best service following service standards and being able to satisfy the parties served. KPPBC TMP C Pasar Baru Post Office in carrying out its duties and functions to realize its vision and mission is required to realize good governance and continue to maintain and improve service quality to be able to provide excellent service by referring to the provisions of the applicable Customs and Excise Law. The purpose of this study is to analyze the quality of public services for imported goods sent for use in realizing excellent service at KPPBC TMP C Pasar Baru Post Office in 2018. The analytical method used in this study is the descriptive analysis by conducting interviews with various informants such as users services, academics, or tax authorities. The results of the study indicate that there is still a lack of service quality and service performance achievements in realizing excellent service, namely: average service performance achievements, have not achieved very good performance; the quality of physical evidence services is still lacking, among others: there are no facilities for service users with special needs; there is no television monitor in the service room related to the mechanism or methods of managing consignments; less stable internet network facilities; the facilities for implementing PIB PDE (online) are not yet ready; and service rooms that are less clean, tidy and comfortable; the quality of service reliability is still lacking, among others: lack of discipline of officers for absenteeism in the system and being at the place of duty during working hours; have not implemented PIB service by PDE (online); unclear information service telephone number; the quality of responsiveness is still lacking, among others: slow response to questions via email and lack of socialization and education to the public.